Bone health and hyperglycemia in pediatric populations. (2nd October 2020) - Bilinski, Wojciech J.; Paradowski, Przemyslaw T.; Sypniewska, Grazyna
Abstract: The impact of prediabetes and diabetes on skeletal health in the context of increased risk of fragility fractures in adults has been studied recently. However, the prevalence of diabetes, overweight, and obesity have also increased in younger subjects. Current data concerning bone metabolism based on assessment of markers for bone turnover and of bone quality in diabetes patients in diverse age groups appears to be inconsistent. This review synthesizes the current data on the assessment of bone turnover based on the use of circulating bone markers recommended by international organizations; the effects of age, gender, and other factors on the interpretation of the data; and the effects of type 1 and type 2 diabetes as well as hyperglycemia on bone quality and turnover with particular emphasis on the pediatric population. Early intervention in the pediatric population is necessary to prevent the progression of metabolic disturbances that accompany prediabetes and diabetes in the context of common low vitamin D status that may interfere with bone growth.